Teaching Computer Science: An Exploration of Habits of Mind - Lauren Hays; Jenna Kammer (The Advocate, 2021)
Previous research has indicated that many K-12 computer science teachers do not have a background in computer science education. This means, computer science teachers are not necessarily using established habits of mind they learned from their own studies. The purpose of this study is to understand more about the habits of mind needed by computer science educators, and students, who often have varying levels of ability and knowledge of computer science. We answer the following research questions: How do teachers of computer science use teaching strategies to develop the habits of mind needed for computing? What habits of mind do teachers of computer science name as important for teaching? What habits of mind do teachers of computer science name as important for learning? To answer the research questions, we used narrative analysis. Findings showed that the backgrounds of computer science teachers greatly impacted their pedagogy and the habits of mind used.
Keywords: habits of mind; computer science education; teaching strategies; pre-service teacher programs